Performance of constructed wetland system for public water supply - Elias, J. M.; Salati Filho, E.; Salati, E. (My University, 2001)
The project is being conducted in the town of Analândia, São Paulo, Brazil. The constructed wetlands system for water supply consists of a channel with floating aquatic macrophytes, HDS system (Water Decontamination with Soil - Patent PI 850.3030), chlorinating system, filtering system and distribution. The project objectives include investigating the process variables to further optimize design and operation factors, evaluating the relation of nutrients and plants development, biomass production, shoot development, nutrient cycling and total and fecal coliforms removal, comparing the treatment efficiency among the seasons of the year; and moreover to compare the average values obtained between February and June 1998 (Salati et al., 1998) with the average obtained for the same parameters between March and June 2000. Studies have been developed in order to verify during one year the drinking quality of the water for the following parameters: turbidity, color, pH, dissolved oxygen, total of dissolved solids, COD, chloride, among others, according to the Ministry of Health's Regulation 36. This system of water supply projected to treat 15 L s-1 has been in continuous operation for 2 years, it was implemented with support of the National Environment Fund (FNMA), administered by the Center of Environmental Studies (CEA-UNESP), while the technical supervision and design were performed by the Institute of Applied Ecology. The actual research project is being supported by FAPESP.
Keywords: Aquatic macrophytes; Constructed wetlands; Filtering soil; Public water supply; Biomass; Chlorine; Color; Oxygen; pH effects; Potable water; Turbidity; Water quality; Water supply systems; Dissolved solids; Wetlands; ammonia; chloride; chlorine; drinking water; hypochlorite; nitrate; nitrite; nitrogen; oxygen; phosphorus; vermiculite; constructed wetland; developing world; performance assessment; water quality; water supply; macrophyte; aquatic flora; biofilter; biomass; Brazil; chemical oxygen demand; chlorination; color; conference paper; disinfection; ecology; environmental parameters; feces microflora; filtration; nonhuman; nutrient; pH; plant; public health; seasonal variation; turbidity; waste water management; waste water recycling; water contamination; water flow; water sampling; water treatment; wetland; Ecosystem; Enterobacteriaceae; Filtration; Nitrogen; Phosphorus; Plants; Soil; Water Movements; Water Purification; Water Supply